Characterisation of a novel plasmid containing a florfenicol resistance gene in Haemophilus parasuis. (April 2018) - Zhang, J.S.; Xia, Y.T.; Zheng, R.C.; Liang, Z.Y.; Shen, Y.J.; Li, Y.F.; Nie, M.; Gu, C.; Wang, H.
Highlights: A novel plasmid was isolated from a florfenicol-resistant Haemophilus parasuis strain from a pigs in eastern China. The plasmid may be derived from pHPS1019 by insertion of floR and lysR genes as a result of a recombination event. This confirms that florfenicol resistant H. parasuis is present in China. Abstract: Thirty clinical isolates of H. parasuis from pig farms in eastern China were screened for antimicrobial susceptibility. A novel plasmid, designated pHPSGC, was extracted from one isolate with evidence of resistance (elevated minimum inhibitory concentration) to florfenicol. DNA sequencing demonstrated that pHPSGC (5297 base pairs) contains three open reading frames (ORFs), corresponding to the genes rep, floR and lysR . The rep gene of pHPSGC shared 99% sequence identity with the rep gene of pHPS1019. In addition, the region containing floR and lysR in pHPSGC shared 99% similarity with the corresponding region of pCCK381. pHPSGC may be derived from a recombination event between pHPS1019 and pCCK381. A florfenicol resistance gene in H. parasuis may have been transferred via recombination between different plasmids.